Selective Laser Melting Of Nickel Titanium Shape Memory Alloy - Leong, Kah Fai (2016)
Nickel titanium (NiTi) is a type of shape memory alloy (SMA) that is difficult to process by conventional manufacturing methods. Thus, Selective Laser Melting (SLM), which is a form of additive manufacturing technology, has been proposed as a potential solution. In this paper, different NiTi samples have been fabricated by using the SLM. The laser power and laser scanning speed were varied from 10 to 100 W and from 100 to 6000 mm/s respectively while keeping the rest of the process parameters as constant. The samples with the highest bulk densities and dimensional accuracy were found to be in the range from 50 to 60 W and from 3100 to 4000 mm/s. These samples were then subjected to differential scanning calorimetry (DSC) testing to determine the presence of phase transformation.